PENGARUH KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia yang terdaftar di Bursa Efek Indonesia Periode 2016-2020) - maesaroh, maesaroh; Abu Hanifah, Imam; Ismawati3, Iis (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of environmental performance on firm value, environmental performance on financial performance, financial performance on firm value through financial performance as an intervention variable in manufacturing companies in the basic and chemical industrial sectors listed on the Indonesia Stock Exchange for the 2016-2020 period. The method used in this research is descriptive method. The sample selection method used in this study is the purposive sampling method, obtained 65 samples of basic and chemical industrial sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The results of this study indicate that there is an influence between environmental performance on firm value, there is an influence between financial performance on firm value, there is no influence between environmental performance on financial performance and financial performance is unable to mediate between environmental performance and firm value